A micromechanics based constitutive model for fibre reinforced cementitious composites. (April 2017) - Mihai, Iulia C.; Jefferson, Anthony D.
Abstract: A new constitutive model for fibre reinforced cementitious composites based on micromechanical solutions is proposed. The model employs a two-phase composite based on the Eshelby matrix-inclusion solution and the Mori–Tanaka homogenization scheme and also simulates directional microcracking. An exterior point Eshelby based criterion is employed to model crack-initiation in the matrix-inclusion interface. Microcrack surfaces are assumed to be rough and able to regain contact under both normal and shear displacements. Fibres are included into the formulation in both cracked and uncracked conditions. Once cracks start to develop, the crack-bridging action of fibres is simulated using a local constitutive equation that accounts for the debonding and pull-out of fibre groups with different orientations. It is shown that the combination of the rough microcrack and fibre-bridging sub-models allows microcracking behaviour deriving from both tensile and compressive loads to be modelled in a unified manner. This ability to model tensile and compressive behaviour using the same micromechanical mechanisms is considered to be a particularly attractive feature of the formulation, which removes the need for multi-parameter triaxial yield surfaces and evolution functions that bedevil many competitor models. The model is successfully validated using a series of examples based on experimental test data.